2016
DOI: 10.1016/j.optcom.2016.04.015
|View full text |Cite
|
Sign up to set email alerts
|

Plasmonic nanopore-based platforms for single-molecule Raman scattering

Abstract: a b s t r a c tWe propose and demonstrate a novel plasmonic nanopore platform based on a bowtie-nanopore structure, for single-molecule sensing. In this nano-structure, nano-bowties are integrated with solidstate nanopores to provide localized surface plasmon resonances for signal enhancement. We design and optimize the nano-structure by tuning both the bowtie gap and the bowtie angle, and investigate their influences on field enhancement, thereby achieving single-molecule sensitivity. In addition, we study th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 28 publications
1
3
0
Order By: Relevance
“…Overall, we observed that |E max /E 0 | values were proportional to the sharpness of the triangle vertices due to the lightning rod effect (which have been explained in the section for figure 3). Similar results have been reported for nanostructures in the shape of pyramids and bowties [54][55][56].…”
Section: E-field Enhancement Analysissupporting
confidence: 89%
“…Overall, we observed that |E max /E 0 | values were proportional to the sharpness of the triangle vertices due to the lightning rod effect (which have been explained in the section for figure 3). Similar results have been reported for nanostructures in the shape of pyramids and bowties [54][55][56].…”
Section: E-field Enhancement Analysissupporting
confidence: 89%
“…[8] In the past 10 years, we have witnessed a growing interest in developing different types of plasmonic nanopores for single nanoparticle or molecule detection and sequencing, and more recently to achieve single protein resolution. [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] In most cases, the fabrication of sub-10 nm pores requires complex multi-step processes, including Transmission Electron Microscopy (TEM)assisted sculpturing of the membrane where the plasmonic nanostructures are prepared by using other techniques, such as focus-ion-beam or electron-beam lithography (FIB or EBL, respectively). [29] Intriguing alternative strategies for plasmonic nanopore fabrication have been reported: for instance, optical control of the dielectric breakdown of the membrane has been demonstrated by several groups, [18,[30][31][32] and more recently the use of laser-driven fabrication of nanometric pores received significant interest within the community.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 As a result of its two strong enhancement mechanisms consisting of electromagnetic (EM) and chemical (charge transfer (CT)) enhancements, 4,5 SERS is an ultrasensitive spectroscopic technique with great potential for use in high-throughput detection and obtaining rich structural information. [6][7][8][9][10][11] SERS is a versatile tool that has been used in numerous fields, [12][13][14][15][16][17][18][19][20][21][22][23][24] including the characterization of compounds and materials, 12,13 single molecule detection, [14][15][16][17][18] immunoassays, [19][20][21] and mechanistic research. [22][23][24] SERS exhibits several advantages: it is non-destructive, rapid, and ultrasensitive and provides detailed molecular fingerprint information.…”
Section: Introductionmentioning
confidence: 99%